2007
DOI: 10.1016/j.joca.2006.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine modulates chondrocyte proliferation, matrix synthesis, and gene expression

Abstract: Results indicate that culture conditions play a significant role in determining the effect of GlcN on chondrocytes, explaining both the previously reported beneficial and deleterious effects of this sugar. The ability of GlcN to alter TGF-beta1 signaling provides a biochemical mechanism for GlcN activity on chondrocytes that up to now has remained elusive. The observed anabolic effect of optimal GlcN concentrations on chondrocytes may be useful in formulating effective cartilage repair strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 40 publications
4
77
1
Order By: Relevance
“…The effect, however small, may be due to an increase in collagen production by chondrocytes in the supplemented groups. 22 Tiku et al 23 showed that treatment of chondrocytes with a similar concentration of glucosamine prevents in vitro collagen degradation over time. More likely, the higher collagen content may reflect the fact that the supplemented group was stiffened because of a rise in PG content and yielded less matrix damage.…”
Section: Discussionmentioning
confidence: 99%
“…The effect, however small, may be due to an increase in collagen production by chondrocytes in the supplemented groups. 22 Tiku et al 23 showed that treatment of chondrocytes with a similar concentration of glucosamine prevents in vitro collagen degradation over time. More likely, the higher collagen content may reflect the fact that the supplemented group was stiffened because of a rise in PG content and yielded less matrix damage.…”
Section: Discussionmentioning
confidence: 99%
“…The volume of the acellular space between the bilayer, however, needs to be optimized properly, as we have observed the distance-dependent response of co-cultured cells. In our bilayer PEODA hydrogel system with approximate 10-nm pore size, when 40 l of acellular space, instead of 20 l, was used in between co-cultured cells, no significant effect of co-culture has been observed (data not shown) [33]. This result indicates the importance of close proximity between cocultured cells.…”
Section: Discussionmentioning
confidence: 74%
“…Although GlcN is a well-tolerated monosaccharide that is naturally made from glucose and glutamine in the body [13], a few studies have reported that large doses of GlcN induce cell death in chondrocytes and several malignant cell lines [22][23][24][25]. To examine the effect of GlcN on viability of human ESCs, human ESC-Ts [26] were cultured for 3, 6, or 9 days in the presence of 0, 2.5, or 5 mM GlcN, and the MTT assay [27] was used to determine cell viability and proliferation.…”
Section: Glucosamine Is Not Toxic To Human Escsmentioning
confidence: 99%